Iron filings in tea and its impact on the quality attributes of made tea and tea liquor - Baby, U.I. (Journal of Plantation Crops, 2020)
Presence of iron filings in made tea (MT) is a serious issue in the tea industry with the implementation of FSSAI regulations. In this scenario, the estimation of iron filings in tea is a critical operation. Unfortunately, the widely accepted method of analysis as per IS 3633 is having a lot of limitations to obtain a reproducible result. Attempts were made to quantify the possible factors affecting the accuracy of the result. Critical attempts were also made to investigate the impact of iron filings on the quality attributes of made tea as well as the tea liquor. Other aspects like adulteration of tea with iron filings and its possible health hazards are also discussed.